Polyphenolic Antioxidants from Agri-Food Waste Biomass - Makris, Dimitris (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The re-use of industrial food residues is essential in the general framework of rational waste handling and recycling, which aims at the minimizing environmental impact of food production and producing functional food ingredients. Agri-food processing waste has long been considered a valuable biomass with a significant polyphenol load and profile. Polyphenols, aside from being powerful antioxidants that confer inherent stability to a variety of foods, may possess versatile bioactivities including anti-inflammatory and chemopreventive properties. The valorization of agri-food waste as a prominent source of polyphenols stems from the enormous amount of food-related material discharged worldwide and the emerging eco-friendly technologies that allow high recovery, recycling, and sustainable use of these materials. This book addresses the concept of recovering natural polyphenolic antioxidants from waste biomass generated by agri-food and related industrial processes and presents state-of-the-art applications with prospect in the food, cosmetic, and pharmaceutical industries.